2017
DOI: 10.1002/prca.201700048
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Diagnostic and Therapeutic Potentials of Human Hair Proteomics

Abstract: The use of noninvasive human substrates to interrogate pathophysiological conditions has become essential in the post- Human Genome Project era. Due to its high turnover rate, and its long term capability to incorporate exogenous and endogenous substances from the circulation, hair testing is emerging as a key player in monitoring long term drug compliance, chronic alcohol abuse, forensic toxicology, and biomarker discovery, among other things. Novel high-throughput 'omics based approaches like proteomics have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 162 publications
0
9
0
Order By: Relevance
“…In 2018, a review regarding human hair proteomics in terms of its diagnostic ability and therapeutic potentials was published and critically discussed about identification of possible biomarkers of diseases utilizing hair as a substrate [52]. They suggested that further investigations were needed to establish "a disease-specific human hair proteome database".…”
Section: Intoxication and Abuse Of Drugsmentioning
confidence: 99%
“…In 2018, a review regarding human hair proteomics in terms of its diagnostic ability and therapeutic potentials was published and critically discussed about identification of possible biomarkers of diseases utilizing hair as a substrate [52]. They suggested that further investigations were needed to establish "a disease-specific human hair proteome database".…”
Section: Intoxication and Abuse Of Drugsmentioning
confidence: 99%
“…Currently, forensic proteomics is in the early stages of development. An increasing number of studies have used proteomics in forensics, such as identification of tissue and body fluid [12][13][14], identification and quantification of protein toxins [15,16], human individualization [17,18], detection of protein drugs and hormones in sports [19,20], and discrimination of wild strains and laboratory-adapted strains of bacteria [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Hair contains 65-85% proteins, 15-35% water, 1-9% lipids, and 0.1-5% pigments like melanin and trace elements (11). Constantly growing scalp hair incorporates both endogenous and exogenous proteins in a time-averaged chronological manner (12), unlike any other biospecimens (13). Therefore it is used for monitoring drug exposures, heavy metals, or other environmental toxins (14).…”
Section: Introductionmentioning
confidence: 99%